The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/modl.12556
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Whose Bilingualism? A Critical Policy Analysis of the Seal of Biliteracy

Abstract: The Seal of Biliteracy is as an initiative to incentivize and credentialize bi‐/multilingualism in K–12 education in the United States. While it has been widely celebrated as a positive development in U.S. educational language policy, it is important to consider to what extent marginalized students benefit from this initiative. This critical policy analysis explores possible inequities in the way that the Seal has been promoted, enacted in policy, and implemented in schools, focused primarily on California. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 29 publications
(44 reference statements)
0
51
0
Order By: Relevance
“…First, researchers have suggested that there is differential access to seals within states, with availability tilted toward wealthier school districts and limited in less well‐resourced ones. For instance, Subtirelu et al (2019) reported in their analysis of California seal data that some schools, especially whiter, wealthier schools with fewer English learners, were more likely to offer seal recognition than others. Second, at least in some states, there is evidence of inequitable and uneven standards, with the proficiency levels in English placed higher than those needed to demonstrate proficiency in foreign/world languages.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…First, researchers have suggested that there is differential access to seals within states, with availability tilted toward wealthier school districts and limited in less well‐resourced ones. For instance, Subtirelu et al (2019) reported in their analysis of California seal data that some schools, especially whiter, wealthier schools with fewer English learners, were more likely to offer seal recognition than others. Second, at least in some states, there is evidence of inequitable and uneven standards, with the proficiency levels in English placed higher than those needed to demonstrate proficiency in foreign/world languages.…”
Section: Related Literaturementioning
confidence: 99%
“…For instance, English‐speaking students in California can demonstrate their proficiency in a language other than English by completing four years of foreign language classes with at least a “B” average and an oral proficiency exam or passing an AP or International Baccalaureate exam. Subtirelu et al (2019) suggest that the path to be verified as biliterate might be more challenging for English learners, who must take formal exams to assess their multilingual ability. And third, in many states, the availability and nature of the assessments are potentially biased toward English speakers who are studying a widely taught world language such as Spanish or French (Heineke et al, 2018).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…It was intended to serve as a recognition of both English learners' (ELs) abilities in their HLs and English native speakers' abilities in world languages (DeLeon, 2014). If responsibly implemented, the SoBL has the potential to level some of the inequities between ELs and world language learners in U.S. schools, provided that the goal of countering the historic marginalization of language‐minoritized students in public education becomes an explicit priority (Subtirelu, Borowczyk, Thorson Hernández, & Venezia, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, it is important for SoBL administrators to ensure access for speakers of languages not frequently offered through mainstream high schools, since a policy that advocates for the celebration and recognition of the United States' bilingual resources must strive to acknowledge the country's linguistic diversity in full. Multiple studies (Heineke, Davin, & Bedford, 2018; Heineke, Davin, & Dávila, 2019; Subtirelu et al, 2019) have concluded that local policies and practices around the SoBL tend to inadvertently advantage English‐dominant students, particularly in the following ways: (a) certain states ask ELs to provide more sources of evidence to demonstrate their English proficiency than other SoBL candidates, (b) the level of English proficiency demanded is generally higher than that of the other language, and (c) the standardized tests required to demonstrate proficiency for the SoBL are overwhelmingly designed for students studying in foreign or world language classes, potentially disadvantaging heritage speakers. The purpose of this paper is to highlight how partnerships with community‐based institutions can serve as important avenues for expanding access to the SoBL, particularly for heritage speakers.…”
Section: Literature Reviewmentioning
confidence: 99%